Optimization of roughing operations in cnc machining for rapid manufacturing processes - Osman, Muhammed; Case, Keith; Watts, Darren (Cranfield University Press, 2013)
This paper presents a method for optimizing roughing operations in CNC machining particularly for parts production through a subtractive rapid manufacturing process. The roughing operation in machining is primarily used to remove the bulk of the material and to approximately shape the workpiece towards the finish form. The manufacturing process described utilizes a 3-axis CNC machine with an indexable 4th axis device that is used to hold and rotate the workpiece. The method used is derived from the multiple approaches in roughing operations that differ in the number and the angle of the orientations. Most of the machining parameters are generalized throughout the process to allow some automation in generating the machining program. Overall, the performance of each of the approaches is evaluated based on the lowest machining time to produce the part.
Keywords: Roughing operation; CNC machining; Rapid manufacturing